2016
DOI: 10.1111/jcmm.12822
|View full text |Cite
|
Sign up to set email alerts
|

Ambient particulate matter exposure and cardiovascular diseases: a focus on progenitor and stem cells

Abstract: Air pollution is a major challenge to public health. Ambient fine particulate matter (PM) is the key component for air pollution, and associated with significant mortality. The majority of the mortality following PM exposure is related to cardiovascular diseases. However, the mechanisms for the adverse effects of PM exposure on cardiovascular system remain largely unknown and under active investigation. Endothelial dysfunction or injury is considered one of the major factors that contribute to the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 156 publications
(201 reference statements)
0
19
0
Order By: Relevance
“…Current studies of effects of PM 2.5 exposure on BMSCs differentiation are limited, and mainly focus on endothelial progenitor cells (EPCs), which play a critical role in maintaining the structural and functional integrity of vasculature. It has been reported that PM 2.5–10 exposure significantly suppressed the number and function of stem cells (SCs) and EPCs in animals and humans [ 8 10 ]. Nevertheless, the mechanisms for the detrimental effects of PM on EPCs remain to be fully defined.…”
Section: Introductionmentioning
confidence: 99%
“…Current studies of effects of PM 2.5 exposure on BMSCs differentiation are limited, and mainly focus on endothelial progenitor cells (EPCs), which play a critical role in maintaining the structural and functional integrity of vasculature. It has been reported that PM 2.5–10 exposure significantly suppressed the number and function of stem cells (SCs) and EPCs in animals and humans [ 8 10 ]. Nevertheless, the mechanisms for the detrimental effects of PM on EPCs remain to be fully defined.…”
Section: Introductionmentioning
confidence: 99%
“…PM 2.5 can have negative effects on air quality and threatens human health. Furthermore, it can have effects on tissue-specific stem progenitor cells [2,3]. However, little is known about the mechanisms underlying the effects of PM 2.5 on stem progenitor cells, particularly hematopoietic stem progenitor cells (HSPCs).…”
Section: To the Editormentioning
confidence: 99%
“…17 – 20 In addition, air pollution is associated with inflammation around the bronchi, which may increase systemic inflammation and oxidative stress leading to obesity. 21 Animal experiments showed that air pollution can lead to weight gain and cardiorespiratory and metabolic dysfunction. 22 …”
Section: Introductionmentioning
confidence: 99%